Reading-writing interface among UPLB Eng 1 students - Grande, Eric Joyce DC (UP Los Baños Journal, 2009)
This study looked into the reading skill of 68 ENG 1 (College English) students of Second Semester Academic Year 2008-2009. In particular, it assessed their reading skill at perceptive/receptive phase through a self-report method. It also assessed their reading skill at productive phase through a performance test. Lastly, it described or categorized their reading skill using a holistic rubic, which is based on Grade's six general component skill and knowledge areas. Results show that the respondents' reading skill at perception or reception phase is at 31.19, which is classified as low survival. Meanwhile, their reading skill at production phase is at 21.89, which is classified as low transitional.